PERAN KERJASAMA ANTARA INTERPOL INDONESIA DENGAN MALAYSIA DITINJAU DARI PERSPEKTIF HUKUM INTERNASIONAL - Okky Wiratama; Sutiarnoto Sutiarnoto; Jelly Leviza (Journal of USU International Law, 2013)
ABSTRACT The trans-national criminal that passes the national border only can be caught by authorized law officer and one of them is Interpol. ICPO-Interpol as organization of Police in the world has a National Central Bureau (NCB) in each state as member. The existence of NCB or its representative in each state will enable the police performance in seek, and arrest the international fugitive. The method of this research is a descriptive analytic method and applies the normative law approach refer to the law norm, especially the international law norm and described into the general section to the specific section based on the primary law, secondary law material and tertiary law material. The data was collected by library study. In seek and arrest the transnational criminal needs a mutual cooperation between polices in any nations. The mutual cooperation between Indonesian Interpol and Malaysia in eradicate the transnational crime enforced in three agreements. First, the extradition contract between Republic of indonesia and Government of Malaysia that validated in Act No. 9 of 1974. Second, is a mutual agreement in criminal code or that known as Mutual Legal Assistance in Criminal Matters (MLA). Third, it is a Memorandum of Understanding between the Government of Republic of Indonesia and Malaysia about the narcotic. Although a mutual cooperation between Interpol of Indonesia and Malaysia had enforced in an agreement, but the agreement is not yet effective, because there are many weakness on the agreement. Therefore, an effective cooperation between both of nations is an informal cooperation through diplomatic relations. Keywords : Interpol, Mutual cooperation , Interpol of Indonesia